Application of mesenchymal stem/stromal cells in periodontal regeneration: Opportunities and challenges - Pan Gao; Mikihito Kajiya; Souta Motoike; Makoto Ikeya; Jingmei Yang (Elsevier, 2024)
Guided tissue regeneration (GTR) has been widely used in the periodontal treatment of intrabony and furcation defects for nearly four decades. The treatment outcomes have shown effectiveness in reducing pocket depth, improving attachment gain and bone filling in periodontal tissue. Although applying GTR could reconstruct the periodontal tissue, the surgical indications are relatively narrow, and some complications and race ethic problems bring new challenges. Therefore, it is challenging to achieve a consensus concerning the clinical benefits of GTR. With the appearance of stem cell-based regenerative medicine, mesenchymal stem/stromal cells (MSCs) have been considered a promising cell resource for periodontal regeneration. In this review, we highlight preclinical and clinical periodontal regeneration using MSCs derived from distinct origins, including non-odontogenic and odontogenic tissues and induced pluripotent stem cells, and discuss the transplantation procedures, therapeutic mechanisms, and concerns to evaluate the effectiveness of MSCs.